REVITALISASI PASAR RAKYAT DAN DAMPAKNYA TERHADAP KEPUASAN DAN PENDAPATAN PEDAGANG - SUDJILAH - (STIE Indonesia Malang, 2020)
The transition from centralized to decentralization, every region implement autonomy including the management of people's markets. Based on Regulation of the Minister of Trade No. 56 / M-DAG / PER / 9/2014 the term